Strategies and tactics in organic synthesis : Vol. 11 - Harmata, Michael, 1959- (Oxford : Academic Press, 2015)
Strategies and Tactics in Organic Synthesis provides a forum for investigators to discuss their approach to the science and art of organic synthesis. Rather than a simple presentation of data or a secondhand analysis, this classic provides stories that vividly demonstrate the power of the human endeavor known as organic synthesis and the creativity and tenacity of its practitioners. Firsthand accounts of each project tell of the excitement of conception, the frustration of failure, and the joy experienced when either rational thought or good fortune gives rise to the successful completion of a project. This book series shows how synthesis is really done. Readers will be educated, challenged, and inspired by these accounts, which portray the idea that triumphs do not come without challenges. This innovative approach also helps illustrate how challenges to further advance the science and art of organic synthesis can be overcome, driving the field forward to meet the demands of society by discovering new reactions, creating new designs, and building molecules with atom and step economies that provide functional solutions to create a better world.
Includes index.
Online resource; title from title details screen (ScienceDirect, viewed August 18, 2015).
Keywords: Organic compounds -- Synthesis; SCIENCE / Chemistry / Organic; Organic compounds -- Synthesis; Electronic books